Treatment with fibrates is associated with higher LAL activity in dyslipidemic patients. (September 2019) - Pavanello, Chiara; Baragetti, Andrea; Branchi, Adriana; Grigore, Liliana; Castelnuovo, Samuela; Giorgio, Eleonora; Catapano, Alberico L.; Calabresi, Laura; Gomaraschi, Monica
Graphical abstract: Abstract: Lysosomal acid lipase (LAL) is responsible for the hydrolysis of cholesteryl esters (CE) and triglycerides (TG) within the lysosomes; generated cholesterol and free fatty acids (FFA) are released in the cytosol where they can regulate their own synthesis and metabolism. When LAL is not active, as in case of genetic mutations, CE and TG accumulate in the lysosomal compartment, while the lack of release of cholesterol and FFA in the cytosol leads to an upregulation of their synthesis. Thus, LAL plays a central role in the intracellular homeostasis of lipids. Since there are no indications about the effect of different lipid-lowering agents on LAL activity, aim of the study was to address the relationship between LAL activity and the type of lipid-lowering therapy in a cohort of dyslipidemic patients. LAL activity was measured on dried blood spot from 120 patients with hypercholesterolemia or mixed dyslipidemia and was negatively correlated to LDL-cholesterol levels. Among enrolled patients, ninety-one were taking one or more lipid-lowering drugs, as statins, fibrates, ezetimibe and omega-3 polyunsaturated fatty acids. When patients were stratified according to the type of lipid-lowering treatment, i.e. untreated, taking statins or taking fibrates, LAL activity was significantly higher in those with fibrates, even after adjustment for sex, age, BMI, lipid parameters, liver function, metabolic syndrome, diabetes and statin use. In a subset of patients tested after 3 months of treatment with micronized fenofibrate, LAL activity raised by 21%; the increase was negatively correlated with baseline LAL activity. Thus, the use of fibrates is independently associated with higher LAL activity in dyslipidemic patients, suggesting that the positive effects of PPAR-α activation on cellular and systemic lipid homeostasis can also include an improved LAL activity.